2011
DOI: 10.2174/1874325001105010361
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment of Moderate Lumbar Spinal Stenosis with the Superion® Interspinous Spacer

Abstract: Purpose:We evaluated the safety and effectiveness of the minimally invasive Superion® Interspinous Spacer (VertiFlex, Inc., San Clemente, CA) in patients with moderate LSS.Methods:This single-arm prospective study enrolled 121 patients with moderate LSS between February 2008 and August 2009 and were followed up at 1 (n=111), 3 (n=96), 6 (n=81), and 12 (n=52) months. All patients were treated with the Superion Interspinous Spacer. Main outcomes were back function with the Oswestry Disability Index (ODI), extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The clinical outcomes with the Superion device in this clinical trial are comparable to those reported in the study of Bini and colleagues who reported 1-year outcomes of 52 patients treated with the Superion device for moderate LSS [28]. In that study, axial pain severity improved from 6.9 ± 1.1 at pretreatment to 3.4 ± 1.5 at 1 year, which represented a 49% improvement ( P < 0.001).…”
Section: Discussionsupporting
confidence: 84%
“…The clinical outcomes with the Superion device in this clinical trial are comparable to those reported in the study of Bini and colleagues who reported 1-year outcomes of 52 patients treated with the Superion device for moderate LSS [28]. In that study, axial pain severity improved from 6.9 ± 1.1 at pretreatment to 3.4 ± 1.5 at 1 year, which represented a 49% improvement ( P < 0.001).…”
Section: Discussionsupporting
confidence: 84%
“…Data from the current study as well as from previous studies suggest that mid-term treatment effectiveness with interspinous spacers is comparable to that of open decompression surgery for moderate LSS [ 16 - 18 ]. The primary advantage of interspinous spacers is the minimally invasive approach, which is in stark contrast to the extensive resection of muscle, ligament, and bone that is typically required for traditional open decompression surgery.…”
Section: Discussionsupporting
confidence: 70%
“…The mid-term effectiveness of the Experimental device is comparable to data reported in two previous studies. Bini and colleagues [ 15 ] reported 1-year outcomes of 52 patients treated with the Experimental device for moderate LSS. In that study, axial pain severity improved 49% (p < 0.001), extremity pain severity improved 53% (p < 0.001), and back function improved 64% (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, after the Vertiflex procedure, there were several patients with claudication who ended up undergoing decompressive laminectomy. In a study on Vertiflex, there were no postoperative wound infections or hematoma noted [ 2 ], although another study identified a case of infection that occurred in an out of procedure-related adverse event from the Vertiflex implant [ 13 ]. Reviewing a randomized controlled trial, the incidence of non-healed spinous process fracture was 11.1% with Vertiflex, while healed spinous process fracture incidence was 5.3% [ 14 ].…”
Section: Discussionmentioning
confidence: 99%